Early re-presentations and the potential role of catheter-directed thrombolysis in patients diagnosed with a lower limb deep vein thrombosis: a single-centre experience. (December 2013) - Chandra, E; Ahmadi, M; Bailey, M A; Griffin, K J; Berridge, D C; Coughlin, P A; Scott, D J A
Introduction: Catheter-directed thrombolysis (CDT) for iliofemoral deep vein thrombosis (DVT) restores venous patency, reduces the risk of the post-thrombotic syndrome and may reduce longer term treatment costs. This study assessed the potential role of CDT in patients with DVT with regard to representation following the index event. Methods: A retrospective review of all patients with a positive lower limb DVT scan. Potential suitability of each patient to undergo CDT was based on well-recognized inclusion/exclusion criteria. Results: In total, 1689 patients underwent a DVT-specific lower limb venous duplex. A total of 269 were found to have a DVT. Fifty-three of these patients met the inclusion criteria for CDT (only 2 underwent CDT). Fifty-nine of the 269 patients with an index DVT re-presented to our institution with a venous thromboembolism-related clinical event. These patients were significantly younger than those who did not reattend. A higher proportion of patients who represented were deemed suitable for CDT for the index DVT compared with those who did not represent (17/59 versus 36/210; P = 0.04). Conclusion: This pragmatic study highlights the fact that significant number of patients return to secondary care with actual/perceived complications following initial diagnosis and treatment of a DVT which may have been amenable to CDT.